Résolution des quelques problèmes aux limites d'équations différentielles de type Caputo-Hadamard via la théorie de point fixe - خزان فاطمة / بنين مريم (university of eloued جامعة الوادي, 2024)
يف هذه املذكرة، قمنا بدراسة بعض مسائل احلدية املرتبطة ابملعادالت التفاضلية الكسرية مبعىن كابوتو هدا مارد. بدأان بدراسة فئة من املعادالت التفاضلية الكسرية من نوع ال جتفي يف هذا السياق، أثبتنا بعض النتائج املتعلقة بوجود و وحدانية احللول. مث تعمقنا يف مشاكل احلدية للمعادالت التفاضلية الكسرية ) االبالسيان، حيث قومنا بتأكيد نتائج حول وجود و وحدانية احللول، كما مت إثبات وجود ووحدانية احللول للمشاكل السابقة عن طريق تطبيق مربهنات النقطة الثابتة )ابالخ، شودر، شيفر(، ابإلضافة إىل ذلك، قمنا بتضمي مثالي توضيحيي لكل من املشاكل املناقشة إلثبات صحة الشروط وتربير فعالية النتائج احملصل عليها. In this memory, we have studied some boundary value problems associated with fractional differential equations in the sense of Caputo-Hadamard. We began by examining a class of fractional differential equations of the Langevin type. In this context, we demonstrated certain results concerning the existence and uniqueness of solutions. Next, we focused on the fractional p-Laplacian boundary value problems, where we established the results on the existence and uniqueness of solutions. The existence and uniqueness of the solutions to the previous problems were demonstrated by applying fixed-point theorems (Banach, Schauder, Schaefer). Additionally, we have included two illustrative examples for each of the addressed problems to demonstrate the ]1[ ]2[ validity of the conditions and to justify the effectiveness of the obtained results.
Keywords: عادالت تفاضلية كسرية، وجود الحلول مشتق كسري من نوع كابوتو هادا مارد، تكامل كسري، نقطة ثابتة; Fractional differential equations; existence of solutions; Caputo-Hadamard; .fractional de rivative; fractional integral; fixed point